CHARACTERISTICS OF GONIOMETRY OF POSTURE OF WOMEN OF THE SECOND PERIOD OF MATURE AGE - Grygus, I. M.; Yastremskyi, О. О.; Chepurka, O. Yu. (Rehabilitation and Recreation, 2025)
Introduction. The scientific discourse on posture goniometry in women of the second period of mature age is multifaceted and includes the study of age-related changes, objective assessment using goniometry, analysis of the relationship with other health indicators, and determination of influential factors. An important aspect of the discourse is the development of corrective and preventive measures aimed at maintaining correct posture and preventing its disorders in women of the second period of mature age, which will reduce the risk of developing various diseases and improve their overall well-being.The purpose of the study is to determine the indicators of posture goniometry in women aged40–45 years.Research methods: theoretical analysis and generalization of literary sources; photography and posture analysis, goniometry, pedagogical experiment, methods of mathematical statistics.Results. The studied women aged 40–45 years showed characteristic deviations from the normative values,which indicates the prevalence of changes in the biomechanics of the spine and the position of the head. Thegreatest deviations were observed for the angles α₁ and α₂ (head tilt angles), therefore, the forward displacementof the head has a predominant diagnostic value for assessing possible posture disorders at this age. It was shown that in women with normal posture, more than 57% of the indicators corresponded to the normative values,while in the group with a round back, 100% of women had deviations from the norm in the parameters α₁ and α₂.These differences, confirmed statistically (p < 0,01), allowed us to conclude that women with a round back had a significantly greater forward head tilt (α₁) and a reduced horizontal head tilt angle (α₂) compared to women with normal posture. We also note that age differences between women aged 40–43 and 44–45 within the same groupin terms of posture in goniometric indicators were not detected (p > 0,05), which indicates the relative stability of postural characteristics in the age range studied.Conclusions. An important component of the continuation of the specified scientific discourse is the development and implementation of corrective and preventive measures aimed at maintaining optimal biomechanics of posture and preventing its disorders in women of the second period of mature age, which will help reduce therisk of developing concomitant pathologies and improve their overall functional state of quality.